An In Vitro Catalysis of Tea Polyphenols by Polyphenol Oxidase - Liu, Kunyi; Chen, Qiuyue; Luo, Hui; Li, Ruoyu; Chen, Lijiao; Jiang, Bin; Liang, Zhengwei; Wang, Teng; Ma, Yan; Zhao, Ming (Molecules, 2023)
Tea polyphenol (TPs) oxidation caused by polyphenol oxidase (PPO) in manufacturing is responsible for the sensory characteristics and health function of fermented tea, therefore, this subject is rich in scientific and commercial interests. In this work, an in vitro catalysis of TPs in liquid nitrogen grinding of sun-dried green tea leaves by PPO was developed, and the changes in metabolites were analyzed by metabolomics. A total of 441 metabolites were identified in the catalyzed tea powder and control check samples, which were classified into 11 classes, including flavonoids (125 metabolites), phenolic acids (67 metabolites), and lipids (55 metabolites). The relative levels of 28 metabolites after catalysis were decreased significantly (variable importance in projection (VIP) > 1.0, p < 0.05, and fold change (FC) < 0.5)), while the relative levels of 45 metabolites, including theaflavin, theaflavin-3′-gallate, theaflavin-3-gallate, and theaflavin 3,3′-digallate were increased significantly (VIP > 1.0, p < 0.05, and FC > 2). The increase in theaflavins was associated with the polymerization of catechins catalyzed by PPO. This work provided an in vitro method for the study of the catalysis of enzymes in tea leaves.